Toll-like receptor-mediated immune imbalance in asthma: controversies, breakthroughs, and future directions - Xu, Xinyi; Yu, Ruihan; Yang, Zhuoqun; Li, Chenyu; Xiong, Huabao; Li, Chunxia (Frontiers in Immunology, 2025)
As a chronic inflammatory illness of the respiratory system, asthma occurs due to various factors and is characterized by a T helper 2 (Th2)-skewed immune response, airway hyperresponsiveness, and reversible airflow obstruction. Toll-like receptors (TLRs) perform a “double-edged sword” function in asthma-related immunological dysregulation by recognizing damage-associated molecular patterns and pathogen-associated molecular patterns. In turn, the activation of some TLRs stimulates epithelial cells to release inflammatory cytokines, exacerbating Th2-driven inflammation and contributing to airway remodeling. Certain TLR signals help inhibit allergic responses by inducing type I interferon or regulatory T cells. The TLR family comprises 10 members, each responsible for recognizing the distinct molecular structure of multiple microbial sources. Variations in environmental microbial exposure duration and host genetic background contribute to the complexity of the TLR signaling network during asthma development. In recent years, therapeutic strategies targeting TLRs have shown potential for asthma treatment. However, a comprehensive review of TLRs in asthma is lacking. Therefore, this review sought to examine the functional mechanisms of TLRs and associated signaling cascades in asthma, and explore novel prevention and treatment approaches centered on TLRs modulation.